2013
DOI: 10.1111/jofo.12008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of audio recording system performance for detecting and monitoring songbirds

Abstract: Acoustic recording systems are being used more frequently to estimate habitat occupancy or relative abundance, and to monitor population trends over time. A potential concern with digital recording systems is that changes in technology could affect detectability of birds and cause bias in trend estimates based on counts of birds detected. We evaluated several currently available commercial recording systems ranging from low‐cost multipurpose digital recorders to custom‐designed wildlife recorders (US$250–$7000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 12 publications
4
69
0
3
Order By: Relevance
“…We used SM3 units and did not observe a significant difference in species richness (5.7%) or abundance indices (−3.7%) between human BBS and on-road ARU surveys, but nonsignificant species-specific differences ranged from 17.1% lower to 23.6% higher in human BBS surveys. The observed differences between human surveys and SM1 units, and human surveys and the SM2 and SM3 units likely reflect the higher signalto-noise ratio in the latter units (e.g., Rempel et al 2013). However, we found that human BBS surveys greatly undersampled RUGR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used SM3 units and did not observe a significant difference in species richness (5.7%) or abundance indices (−3.7%) between human BBS and on-road ARU surveys, but nonsignificant species-specific differences ranged from 17.1% lower to 23.6% higher in human BBS surveys. The observed differences between human surveys and SM1 units, and human surveys and the SM2 and SM3 units likely reflect the higher signalto-noise ratio in the latter units (e.g., Rempel et al 2013). However, we found that human BBS surveys greatly undersampled RUGR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing results from human and ARU (Wildlife Acoustic Inc., i.e., Song Meter units) surveys have found both lower (8%-10% fewer species with the SM1 unit; Venier et al 2012, Rempel et al 2013) and similar ARU performances (SM2 unit; Alquezar and Machado 2015, La and Nudds 2016, but see Klingbeil and Willig 2015, Yip, Leston, et al 2017. We used SM3 units and did not observe a significant difference in species richness (5.7%) or abundance indices (−3.7%) between human BBS and on-road ARU surveys, but nonsignificant species-specific differences ranged from 17.1% lower to 23.6% higher in human BBS surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the long deployment period, the recorded vocal activity could not be assessed manually but required an automated call recognition algorithm (Brandes 2008;Digby et al 2013;Rempel et al 2013;Swiston and Mennill 2009). We performed automated analyses of all field recordings with the eXtensible BioAcoustic Tool (XBAT, http://www.xbat.org), a bioacoustic analysis software package for Matlab that includes algorithms for detecting sounds of interest in acoustic recordings.…”
Section: Acoustic Data Processing and Calibrationmentioning
confidence: 99%
“…Las diferencias entre los equipos de grabación están vinculadas con varias características como por ejemplo en la relación señal a ruido, en la calidad y diseño de los circuitos electrónicos, la configuración, la protección del equipo a las condiciones de intemperie, frecuencia de muestreo, filtros de reducción de ruido de fondo y cronogramas de programación [26]. Las ARUs más utilizadas para este fin son los songmeters, sistemas de grabación E3A, teléfonos móviles y accesorios.…”
unclassified
“…En [26] se recomienda que en estudios de corto a mediano plazo se utilicen los mismos equipos por un máximo de cinco años, por diferentes razones primero, debido a que la tecnología cambia rápidamente, es mejor reemplazar con nuevas versiones de equipos y así poder gozar de las mejoras que los fabricantes hayan realizado; segundo, las versiones antiguas de los equipos salen del mercado y esto hace que sea casi imposible mantenerlas.…”
unclassified